The Influence of Work From Home and Work-Life Balance on Job Performance in Employees (Case Study at PT Rata Indonesia) - Natalia Christy; Dian Indiyati (Return : Study of Management, Economic and Bussines, 2024)
Human resources play an important role for an organization or company. Employees as one of the drivers in achieving organizational goals must of course have their needs met so that these employees can provide good reciprocity to the organization. Employees as the main resource for the organization must also be considered for their quality in order to create superior and competent human resources. This study aims to determine the level of work from home and work life balance on job performance in employees and to determine the effect of work from home, work life balance and job performance on PT Rata Indonesia employees. The method used in this research is quantitative and then to describe the research results using descriptive data analysis techniques. The data collection method in this study was by distributing questionnaires. This study uses a Likert scale with a total of 30 statements. The population in this study amounted to 129 employees and the sample in this study used non-probability sampling with saturated sampling technique which sampled the entire population. The findings suggest that companies should support employees in achieving a healthy work-life balance and provide adequate resources for effective work-from-home arrangements to maximize productivity. This study contributes to the understanding of how work arrangements and work-life balance affect employee performance, providing insights for future research and practical implications for human resource management.